2006
DOI: 10.3758/bf03193737
|View full text |Cite
|
Sign up to set email alerts
|

The subjective duration of ramped and damped sounds

Abstract: Two experiments demonstrate that the perceived durations of sounds as long as 1 sec are influenced by the sounds' amplitude envelopes, extending Schlauch, Ries, and DiGiovanni's (2001) observations on sounds of 200-msec duration. Sounds with a monotonic decay (i.e., damped sounds) are heard as substantially shorter than both steady sounds and those with a monotonic increase of level (i.e., ramped sounds). Neither a reaction time (Experiments 1 and 2) nor a staircase (Experiment 2) procedure supported a sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
70
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 28 publications
12
70
1
Order By: Relevance
“…These results are consistent with those reported previously ͑DiGiovanni and Schlauch, 2007;Grassi and Darwin, 2006;Schlauch et al, 2001b͒. That is, damped sounds are perceived as being shorter than ramped sounds of equivalent duration.…”
Section: E Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results are consistent with those reported previously ͑DiGiovanni and Schlauch, 2007;Grassi and Darwin, 2006;Schlauch et al, 2001b͒. That is, damped sounds are perceived as being shorter than ramped sounds of equivalent duration.…”
Section: E Discussionsupporting
confidence: 83%
“…Prior studies have reported results for a variety of auditory phenomena including intensity discrimination ͑Schlauch et al, 1998͒, subjective duration ͑DiGiovanni and Schlauch, 2007;Grassi and Darwin, 2006;Schlauch et al, 2001a, 2001b͒, loudness ͑Irino and Patterson, 1996Neuhoff 1998Neuhoff , 2001Maier et al, 2004;Stecker and Hafter, 2000͒, and tonality ͑Patterson, 1994a. All of these studies, except that on intensity discrimination ͑Schlauch et al, 1998͒, report perceptual differences between ramped and damped stimuli of the same physical duration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major results have been achieved concerning the loudness asymmetries for a ramp duration of 1.8 s. However, recent results showed that the asymmetry still exists for longer durations (Ponsot et al, 2013). Up-ramps are also judged longer than down-ramps of the same physical duration (Schlauch et al, 2001;Grassi and Darwin, 2006;DiGiovanni and Schlauch, 2007;Ries et al, 2008;Grassi and Pavan, 2012). Most studies focused on the perceived duration asymmetry for durations shorter than 1 s. Globally it was found that the difference between the perceived duration of up-and down-ramps decreases as the duration increases from about 50 to 1000 ms (Schlauch et al, 2001;Grassi and Darwin, 2006;Ries et al, 2008;Grassi and Pavan, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Up-ramps are also judged longer than down-ramps of the same physical duration (Schlauch et al, 2001;Grassi and Darwin, 2006;DiGiovanni and Schlauch, 2007;Ries et al, 2008;Grassi and Pavan, 2012). Most studies focused on the perceived duration asymmetry for durations shorter than 1 s. Globally it was found that the difference between the perceived duration of up-and down-ramps decreases as the duration increases from about 50 to 1000 ms (Schlauch et al, 2001;Grassi and Darwin, 2006;Ries et al, 2008;Grassi and Pavan, 2012). In other words, up-ramps are perceived longer than down-ramps for durations up to 1 s. However, DiGiovanni and Schlauch (2007) found an increase in the asymmetry between 50 and 500 ms for broadband noises.…”
Section: Introductionmentioning
confidence: 99%